Probing millicharged particles at an electron beam dump with ultralow-threshold sensors - Rouven Essig; Peiran Li; Zhen Liu; Megan McDuffie; Ryan Plestid; Hailin Xu (Journal of High Energy Physics)
Abstract We propose to search for millicharged particles produced in high-intensity electron beam dumps using small ultralow-threshold sensors. As a concrete example, we consider a Skipper-CCD placed behind the beam dump in Hall A at Jefferson Lab. We compute the millicharged particle flux, including both electromagnetic cascade and meson productions emanating from an aluminum target. We find that the sensitivity of a modest 2 × 14 array of Skipper-CCDs can exceed the sensitivity of all existing searches for millicharged particle masses below 1.5 GeV, and is either competitive or world leading when compared to other proposed experiments. Our results demonstrate that small-scale ultralow threshold silicon devices can enhance the reach of accelerator-based experiments, while fitting comfortably within existing experimental halls.